Peran Kepala Sekolah Dalam Menyelamatkan Ahklak Generasi Muda Melalui Keterampilan Sulam Kasab Berbasis Kearifan Lokal Di Takengon - Loeziana Uce, Hayati, Mashuri, Banta Karollah, Budiman (Bansigom Na Publisher, 2024)
The current development of information and communication technology presents promising opportunities for the development of various aspects of life, especially for teenagers and high school students. However, it also poses serious challenges in preserving and safeguarding the moral values of the younger generation. In this context, school principals play a crucial role in implementing activities that support a positive direction. One such approach is to build character and high integrity towards noble moral values. A step that can be taken is by creating extracurricular activities that utilize technology and craftsmanship to produce products beneficial for daily life, such as the craft of Kasap embroidery in Central Aceh. Activities involving lecturers, students, and stakeholders, such as the International Community Service Program (PKM), aim to disseminate knowledge and raise awareness, especially regarding the roles of academics and school principals in the digital era. The evaluation of the Community Service Program (PKM) activities indicates a positive impact and active participation from the community, contributing to problem-solving and community development. This International Community Service Program makes a tangible contribution to addressing issues related to the morals and ethics of the younger generation, creating a safer digital environment, and aligning with the principles of truth and justice.